Three-dimensional characterization and quantitative research of Malan loess microstructure under seismic loading - Wei, Tingting; Wu, Zhijian; Chen, Yanping; Luo, Liang (Frontiers in Earth Science, 2023)
The deformation and failure of loess in areas of high seismic intensity are closely related to the dynamic vulnerability, which is primarily controlled by the loess microstructure. This study performed a series of dynamic triaxial tests and microstructure tests on intact loess to track and quantitatively characterize the evolution of the three-dimensional microstructure during deformation. The microstructural observations were performed using micro-CT on the samples after varying vibration times. The microstructure parameters (including pore radius, elongation, orientation, coordination number, pore throat area, and channel length) were obtained using a reconstructed pore network model. The results of this study demonstrated that the loess seismic subsidence originated from both compositional and microstructural characteristics. The intact loess had a loose structure with high porosity and limited cementation. Upon cyclic loading, cementation and contact breakdown led to the failure of the loess structure, followed by particle rearrangement. With increasing vibration times, the spaced and inter-aggregate pores became intra-aggregate pores, the pore throat size tended to decrease while the pore number tended to increase, the connectivity tended to weaken, and the shape tended to be long and flat. Pores >28 μm mainly provided spatial conditions for collapse deformation under seismic load. In addition, under the ultimate loading, large-volume cracks occurred inside the sample. The findings of this study provide further insights into loess seismic subsidence from the perspective of three-dimensional microstructures and a research basis for analyzing the stability of loess in relation to construction projects by combining finite and discrete elements.